Tri N (Niteni, Niroake, Nambahake) dalam Pengembangan Kreativitas SBDP Batik Jumputan - Eko; Moh. Rusnoto Susanto; Ana Fitrotun Nisa (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This research aims to investigate the relationship of Tri N (Niteni, Niroake, and Nambahake) in developing students' creativity in SBdP batik jumputan. This research employed descriptive qualitative approach. It describes the implementation of Tri N at SDN 3 Taskombang. The data were collected by applying observation and reviewing documeny. The data were analized by applying Milles and Huberman techniques. It comprises data reduction, data presentation, and verification. The result shows that through the implementation of Tri N, students become more creative and are able to produce innovative works that can be used for daily life.